(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To analyze factors influencing early graft kidney function in living donor transplants at Viet Duc University Hospital. Materials and methods: A prospective descriptive study of patients undergoing routine kidney transplantation from January 2025 to July 2025 at Viet Duc University Hospital. Results: 87 patients received living donor kidney transplants. Donor characteristics: mean age 42 ± 5.2 years, Gender male 55.6%, female 44.4%, BMI 21.4 ± 2.3 kg/m², pre-transplant eGFR: 114 ± 12.5 mL/min/1.73m², cold ischemia time 156 ± 25 minutes, warm ischemia time 6.6 ± 1.2 minutes. Recipient characteristics mean age 36 ± 4.8 years, pre-transplant dialysis duration 5.5 ± 2.1 months, postoperative day 1 creatinine 370 ± 156 μmol/L, urine output in first 2 hours 650 ± 320 mL; complications: acute rejection 2.3%, infection 1.15%. Conclusion: The study demonstrates excellent outcomes of living donor kidney transplantation at Viet Duc Friendship Hospital with low complication rates. Favorable factors include short warm ischemia time (6.6 minutes), acceptable cold ischemia time (156 minutes), and ideal donor characteristics (young age, high eGFR).